Mechanistic insight into the optimal recovery efficiency of CBM in sub-bituminous coal through molecular simulation. (15th April 2020) - Liu, Xiao-Qiang; Li, Meijun; Zhang, Chenghua; Fang, Ronghui; Zhong, Ningning; Xue, Ying; Zhou, Yang; Jiang, Weidong; Chen, Xu-Yang
Graphical abstract: Abstract: In this study, a newly created Fortran program was used to assist in the constructing of a sub-bituminous coal model (SCM). Followed by grand canonical Monte Carlo simulations, the adsorption behaviors of CBM adsorption on dry-/moisture-SCM systems have been systematically studied at different pressure-temperature conditions. A geological model with typical geothermal and pressure gradients was established to investigate the effect of coupled pressure and temperature on the absorption and recovery. As a result, pure-N2 injection has been confirmed to paly a negative role on CH4 recovery, whereas CO2 could effectively improve the CO2 sequestration and CH4 displacement. Meanwhile, the adsorption percentage ( δ ) and the recovery efficiency ( η ) were first put forward in terms of theoretical calculations. The results showed that, the δ was determined by pore size distribution of the SCM, adsorption temperature/pressure, moisture-containing in coal and the types of adsorbates. The value of η C H 4 is 53.07% in dry coal seam, whereas 47.20% is evaluated in moisture coal seam, the corresponding optimum mining depths are 600 m and 800 m, respectively. Remarkably, water-containing in coal seam has an obviously inhibitory effect on simultaneous extraction of coal and gas, and it should be valued in the follow-up studies. Based on this principle, the optimum mining depth for CO2 -ECBM was predicted to be ∼800 m in actual deep coal seams through our geological model. Our results provide a molecular-scale insight into CBM recovery efficiency in coal at different burial depths, and offer useful guidance for realistic exploitation.